Case Study : Mieraezad Bundle Enterprise / Siti Sakinah Zuhari - Zuhari, Siti Sakinah (2020)
The name “Mieraezad Bundle Enterprise” or the one that the owner always use, “Myra Aqilah Bundle” came from the owner’s real business itself that selling the used of goods. Mieraezad Bundle Enterprise is a business that can be categorized as Small Medium Enterprise (SME) which provides used of goods such as mattress, bags, toys and children’s clothes to the customers. The company is specialized in giving many choices to the customers as all of the products are from abroad and the condition of the products are good enough to be sell. With this type of service, the owner cannot run away from achieving her mission that is to improve her business quality and her vision that is serving the customers with pure value creation and of course gives them happiness. Even though the company is still newly established, the financial is stable enough due to the high demand from customers every day. The company plan to expand the business by opening a second branch in the future